PERFORMANCE OF HUMAN RESOURCES DEVELOPMENT AGENCY (BPSDM) OF SOUTHEAST SULAWESI PROVINCE - Abdul Kahar Muzakir Sinapoy (Universitas Halu Oleo, 2021)
This study intends to analyze the impact of work culture and job satisfaction on employee performance at BPSDM Southeast Sulawesi Province. This type of research is explanatory research, with a total sample of 47 respondents. The sample size was determined based on the slovin method, the sampling technique was carried out directly. Data was taken using a questionnaire with a Likert scale. Analysis of the data by descriptive and multiple linear regression. The results of the research prove that work culture has a positive effect on employee performance with a significance number of 0, 000 and t is 43, 757 with a coefficient of 0, 74. Job satisfaction has a positive effect on employee performance with a significance number of 0, 000 and t is 82, 629 and a coefficient of 0, 93. Based on the results of data analysis, it is concluded that work culture and job satisfaction greatly affect employee performance. This shows that the two variables, both work culture and job satisfaction, have been tested to significantly affect employee performance.AbstrakPenelitian ini bermaksud untuk menganalisa akibat aspek budaya kerja serta kepuasan kerja terhadap kinerja pegawai di BPSDM Provinsi Sulawesi Tenggara. Tipe penelitian merupakan eksplanatory research, dengan jumlah sampel sebesar 47 responden. Besar sampel didetetapkan berdasarkan pada metode slovin, teknik penarikan sampel dilakukan secara langsung. Data diambil menggunakan angket dengan skala likert. Analisa data dengan cara deskriptif serta regresi linier berganda. Hasil riset membuktikan kalau budaya kerja mempengaruhi positif terhadap kemampuan pegawai dengan angka signifikansi 0, 000 serta t jumlah sebesar 43, 757 dengan angka koefisien 0, 74. Kepuasan kerja mempengaruhi positif terhadap kinerja pegawai dengan angka signifikansi 0, 000 serta t jumlah sebesar 82, 629 serta angka koefisien 0, 93. Berdasarkan pada hasil analisa data, disimpulkan kalau budaya kerja serta kepuasan kerja sangat mempengaruhi kinerja pegawai. Hal ini menunjukkan bahwa kedua variable tersebut, baik budaya kerja maupun kepuasan kerja teruji secara sognifikan mempengaruhi kinerja pegawai.